เครื่องเติมอากาศแบบกังหันใช้พลังงานแสงอาทิตย์ร่วมพลังงานย้อนกลับสำหรับบ่อปลา - มหาไม้, ปรีชา; วิริยะ, วรวุฒิ; เพชรสุวรรณ, พิสุทธิ์ (Health Science, Science and Technology Reviews, 2014)
งานวิจัยนี้นำเสนอการออกแบบสร้างเครื่องเติมอากาศที่ผิวน้ำแบบกังหันขนาดเล็กสำหรับเพิ่ม ปริมาณออกซิเจนที่ ละลายในน้ำนำไปใช้กับบ่อเลี้ยงปลาที่เป็นบ่อดินขนาด 20 ตารางเมตร พบจุดเด่นของเครื่องเติมอากาศ คือ ใช้พลังงาน ทดแทนจากพลังงานแสงอาทิตย์และพลังงานไฟฟ้าที่เปลี่ยนมาจากพลังงานกลที่หมุนใบกังหัน ใช้เวลาในการทดสอบเป็น เวลา 8 ชั่วโมงและวัดปริมาณออกซิเจนที่ละลายในน้ำทุก 2 ชั่วโมง จากบ่อที่ใช้เครื่องเติมอากาศเปรียบเทียบกับบ่อที่ไม่เติม อากาศจากการทดสอบพบว่า ปริมาณออกซิเจนที่ละลายในน้ำเฉลี่ยต่อชั่วโมงเพิ่มขึ้น 1.537 มิลลิกรัมต่อลิตร กำลังไฟฟ้าที่ ได้จากเซลล์แสงอาทิตย์เฉลี่ย 51 วัตต์ กำลังไฟฟ้าที่ได้จากชุดแปรผันกำลังไฟฟ้าเฉลี่ย 4.9 วัตต์ The paddle wheels aerator used solar and backward energy for fish pound Preecha Mahamai1*, Walrawuth Viriya1 and Pisut Phechsu2 1 Department of Electronics Engineering, Faculty of Engineering, Rajamangala University of Technology Lanna Tak, Tak Province 63000 2 Department of Mechanical Engineering, Faculty of Engineering, Rajamangala University of Technology Lanna Tak, Tak Province 63000 The objective of this research was to design the paddle wheels surface aerator with small and low cost for increasing the amount of dissolved oxygen applied to an eather fish pound measuring 20 square meters. The highlight of the aerator is used renewable solar energy and electrical energy transformed from mechanical energy of the rotating turbine blades. The test eight hours the dissolved oxygen water was measured every 2 hours. Under experimental conditions, the average dissolved oxygen per hour in the water was increased by 1.537 milligrams per liter compared to the control. An average of 51 watts was obtained from the solar cell, while power produced by the generator was 4.9 watts.